Analisis Kesalahan Tata Bahasa dan Diksi para Debator dalam Debat Ilmiah Bahasa Arab Muktamar ITHLA IX - Mahdi, Rijal; Amin, Irsal; Latif, Abdul; Shiddiq, Jamaluddin; Hidayat, Ahmad Fadhel Syakir (Al-Ma‘rifah, 2022)
The object of this research is the Arabic diction of debaters in the scholarly arabic debate competition organized by the Indonesian Arabic Student Association (ITHLA) at the IX 2021 congress. This study aims to explain some of the Arabic diction mistakes made by debaters in the Arabic scientific debate competition in Indonesia. In addition, this study also provides an alternative Arabic diction that should be used when conveying ideas in scholarly debates. This research method is a type of descriptive qualitative research. The source of research data is transcription obtained from two stages, namely observation and documentation. This study shows that there are many grammatical and diction errors used by the debaters. In general, the errors can be classified as follows: Errors in unsuitable use of ḥarf al-jar, errors in the use of vocabulary, country name, adjectives, word construction, singular and plural, error words, junctions, incorrect use of conjunctions, etc. After understanding these grammatical and diction errors, it is hoped that they can improve students’ Arabic skills at the upcoming Arabic scientific debate.